2021
DOI: 10.1371/journal.pone.0250305
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pharmaceutical co-payment increase on the use of social assistance—A natural experiment study

Abstract: Health care out-of-pocket payments can create barriers to access or lead to financial distress. Out-of-pocket expenditure is often driven by outpatient pharmaceuticals. In this nationwide register study, we study the causal relationship between an increase in patients’ pharmaceutical expenses and financial difficulties by exploiting a natural experiment design arising from a 2017 reform, which introduced higher co-payments for type 2 diabetes medicines in Finland. With difference-in-differences estimation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Previous studies revealed coinciding decrease in medication consumption and increase in economic problems. [15][16][17][18] I complement previous evidence by examining financial access to medicines as part of more general patterns of economic hardship. I ask whether austerity coincided with exacerbation of inequalities, and whether hardship related to medications developed differently than other economic problems.…”
Section: Original Researchmentioning
confidence: 87%
“…Previous studies revealed coinciding decrease in medication consumption and increase in economic problems. [15][16][17][18] I complement previous evidence by examining financial access to medicines as part of more general patterns of economic hardship. I ask whether austerity coincided with exacerbation of inequalities, and whether hardship related to medications developed differently than other economic problems.…”
Section: Original Researchmentioning
confidence: 87%
“…Previous studies have suggested an increase in economic difficulties ( Aaltonen, Niemelä, & Prix, 2022 ; Rättö & Aaltonen, 2021 ; Lavikainen, Aarnio, Jalkanen, et al, 2020 ), negative developments in satisfaction of care ( Lavikainen, Aarnio, Niskanen, Mäntyselkä, & Martikainen, 2020 ), and impacts related to the consumption of type 2 antidiabetics ( Lavikainen, Aarnio, Jalkanen, et al, 2020 ; Lavikainen, Aarnio, Niskanen, et al, 2020 ) among individuals with type 2 diabetes after the reform. Regarding insulin consumption, a survey study found responders reporting increased insulin use due to cost ( Lavikainen, Aarnio, Niskanen, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The benchmark regression results are reported in Table 3. Column (1) shows that the estimated coefficient of Policy is 0.0044 but not significant, indicating that China's NCMR pilot policy had no significant impact on residents' medical expenses of outpatients. Column (2) presents that the estimated coefficient of Policy is−0.0213 and significant at the 1% level, indicating that the pilot policy significantly reduced residents' medical expenses of inpatients.…”
Section: Benchmark Regressionmentioning
confidence: 98%
“…The rapid rise of medical expenses will crowd out residents' consumption in other fields, bring about a loss of social welfare, and thus affecting the sustainable development of macro-economy ( 1 , 2 ). Therefore, how to effectively cope with the continuous rising in residents' medical expenses has become a common challenge for the medical systems worldwide, which is also a problem that national medical reform hope to solve ( 3 ).…”
Section: Introductionmentioning
confidence: 99%